Direct Numerical Simulation of Flow and Heat Transfer in a Compressor Blade Passage Across a Range of Reynolds Numbers - Yang Liu; Chenchen Zhao; Lei Zhou; Duo Wang; Hongyi Xu (Aerospace, 2025)
This study employs Direct Numerical Simulation (DNS) to investigate the flow and heat transfer characteristics in a compressor blade passage at five Reynolds numbers (<semantics>Re=1.091×105</semantics>, <semantics>1.229×105</semantics>, <semantics>1.367×105</semantics>, <semantics>1.506×105</semantics>, and <semantics>1.645×105</semantics>). A recent method based on local inviscid velocity reconstruction is applied to define and calculate boundary layer parameters, whereas the Rortex vortex identification method is used to analyze turbulent vortical structures. Results indicate that <semantics>Re</semantics> significantly affects separation bubble size, transition location, and reattachment behavior, thereby altering wall heat transfer characteristics. On the pressure surface, separation and early transition are observed at higher <semantics>Re</semantics>, with the Nusselt number (<semantics>Nu</semantics>) remaining high after transition. On the suction surfaces, separation occurs such that large-scale separation at low <semantics>Re</semantics> reduces <semantics>Nu</semantics>, while reattachment combined with turbulent mixing at high <semantics>Re</semantics> significantly increases <semantics>Nu</semantics>. Turbulent vortical structures enhance near-wall fluid mixing through induced ejection and sweep events, thereby promoting momentum and heat transport. As <semantics>Re</semantics> increases, the vortical structures become denser with reduced scales and the peaks in heat flux move closer to the wall, thus improving convective heat transfer efficiency.